2021
DOI: 10.1101/2021.08.16.456510
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Age-related susceptibility of ferrets to SARS-CoV-2 infection

Abstract: Susceptibility to SARS-CoV-2 and the outcome of COVID-19 have been linked to underlying health conditions and the age of affected individuals. Here we assessed the effect of age on SARS-CoV-2 infection using a ferret model. For this, young (6-month-old) and aged (18-to-39-month-old) ferrets were inoculated intranasally with various doses of SARS-CoV-2. By using infectious virus shedding in respiratory secretions and seroconversion, we estimated that the infectious dose of SARS-CoV-2 in aged animals is ~32 plaq… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…Our study extends the knowledge regarding SARS-CoV-2 infection dynamics in WTD, an animal species with the potential to serve as a reservoir for the virus in the field. We defined that SARS-CoV-2 has a short window of infectivity and transmissibility in WTD, which is similar to what has been described in humans and other animal species [19,21,27,29,[36][37][38], and demonstrated that the virus presents a broad tissue tropism and multiple replication sites in this species. This information is critical to assess the relevance of natural SARS-CoV-2 infections in WTD populations and the potential risk of zoonotic spillback into humans.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Our study extends the knowledge regarding SARS-CoV-2 infection dynamics in WTD, an animal species with the potential to serve as a reservoir for the virus in the field. We defined that SARS-CoV-2 has a short window of infectivity and transmissibility in WTD, which is similar to what has been described in humans and other animal species [19,21,27,29,[36][37][38], and demonstrated that the virus presents a broad tissue tropism and multiple replication sites in this species. This information is critical to assess the relevance of natural SARS-CoV-2 infections in WTD populations and the potential risk of zoonotic spillback into humans.…”
Section: Discussionsupporting
confidence: 67%
“…tigers, lions, mink, cats, dogs, hamsters and ferrets) naturally and/or experimentally infected with the virus, in which characteristic mutations mainly in the S protein have been observed shortly after infection [22][23][24][25]. The findings in WTD can be partially explained by the high degree of homology of the human and deer ACE2 proteins species and in humans [19,[26][27][28][29]. Following infection and replication in these sites, the virus likely disseminates to draining lymph nodes, the lower respiratory (trachea and lung) tract and the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…The first set contained 17 positive and 43 negative serum samples collected from cats infected with SARS-CoV-2 D614G (B.1), Delta (B.1.617.2), or Omicron (B.1.1.529) strain in study described previously (19). The second set contained 10 positive and 37 negative serum samples collected from SARS-CoV-2 isolate NYI67-20 (B.1 lineage) infected ferrets (43).…”
Section: Sample Sourcesmentioning
confidence: 99%